The Effect of Feed Acidification On Protein, Fat, And Cholesterol Content of Meat Broiler Fed Two Different Commercial Diets - Mulyantini S S, Ni Gusti Ayu; Suryatni, Ni Putu Febri (Program Studi Peternakan, Fakultas Pertanian, Sains dan Kesehatan, Universitas Timor, 2025)
The study aimed to analyze the effects of different feed commercials, the level of acidifier, and their interaction on carcass weight, pH of breast meat, protein, fat, and cholesterol content of broiler chickens. A total of 160 broiler chickens (21 day old, mixed of male and female) were randomly allocated to 8 groups with 4 replicates per group, and 5 chickens per replicate. Research methods using a Completely Randomized Design with a 2x4 factorial pattern involving 2 types of commercial diets (Diet A and Diet B), and 3 levels (L) of acidifier (0%, 0,5%, 1%, and 1,5%). The carcass and protein, fat, and cholesterol of breast meat were analyzed on day 35. The results showed, with the increase of acidifier level, the fat and cholesterol content significantly decreased (P<0.05), reaching the lowest value in the levels of acidifier of 1 and 1,5%. Carcass weight and protein content of breast meat were not affected by diets and the level of acidifier. Diets and the interaction between diets and the level of acidifier had no significant effect on all of the parameters measured. In conclusion, the low fat, and low cholesterol content can be obtained when the acidifier level is between 1 and 1,5% regardless of the type of commercial diets.